2023
DOI: 10.1111/zph.13042
|View full text |Cite
|
Sign up to set email alerts
|

Ťahyňa virus—A widespread, but neglected mosquito‐borne virus in Europe

Abstract: Ťahyňa virus (TAHV) is an orthobunyavirus and was the first arbovirus isolated from mosquitoes in Europe and is associated with floodplain areas as a characteristic biotope, hares as reservoir hosts and the mammal‐feeding mosquitoes Aedes vexans as the main vector. The disease caused by TAHV (“Valtice fever”) was detected in people with acute flu‐like illness in the 1960s, and later the medical significance of TAHV became the subject of many studies. Although TAHV infections are widespread, the prevalence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…vexans and Ae. caspius [ 30 , 31 ], the virus has been found in several other mosquito species in different areas [ 9 , 11 ] as recorded also in this study. The detection of TAHV in different mosquitoes implicates the local involvement of different mosquito species, mainly of the Aedes genus, as vector in different ecological settings.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…vexans and Ae. caspius [ 30 , 31 ], the virus has been found in several other mosquito species in different areas [ 9 , 11 ] as recorded also in this study. The detection of TAHV in different mosquitoes implicates the local involvement of different mosquito species, mainly of the Aedes genus, as vector in different ecological settings.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, old serology studies have reported the likely human circulation of the virus in Italy, particularly in wetland areas [ 46 ]. The possible increase of TAHV after flooding events [ 11 , 28 ] makes this virus potentially more dangerous in climate change scenarios, which will cause a probable increase in extreme events, such as exceptionally heavy rainfall. The detection of TAHV at an important level testify a relevant circulation of the virus and implies the potential human infection in the surveyed area, this aspect needs to be investigated, to determine the potential impact of this virus on human health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation